The igapó of the Negro River in central Amazonia: Linking late-successional inundation forest with fluvial geomorphology - Montero, Juan Carlos; Latrubesse, Edgardo M. [UNESP] (Elsevier, 2013)
Despite important progress on Amazonian floodplain research, the flooded forest of the Negro River igapó has been little investigated. In particular, no study has previously focused the linkage between fluvial geomorphology and the floristic variation across the course of the river. In this paper we describe and interpret relations between igapó forest, fluvial geomorphology and the spatial evolution of the igapó forest through the Holocene. Therefore, we investigate the effect of geomorphological units of the floodplain and channel patterns on tree diversity, composition and structural parameters of the late-successional igapó forest. Our results show that sites sharing almost identical flooding regime, exhibit variable tree assemblages, species richness and structural parameters such as basal area, tree density and tree heights, indicating a trend in which the geomorphologic styles seem to partially control the organization of igapó's tree communities. This can be also explained by the high variability of well-developed geomorphologic units in short distances and concentrated in small areas. In this dynamic the inputs from the species pool of tributary rivers play a crucial role, but also the depositional and erosional processes associated with the evolution of the floodplain during the Holocene may control floristic and structural components of the igapó forests. These results suggest that a comprehensive approach integrating floristic and geomorphologic methods is needed to understand the distribution of the complex vegetation patterns in complex floodplains such as the igapó of the Negro River. This combination of approaches may introduce a better comprehension of the temporal and spatial evolutionary analysis and a logic rationale to understand the vegetation distribution and variability in function of major landforms, soil distributions and hydrology. Thus, by integrating the past into macroecological analyses will sharpen our understanding of the underlying forces for contemporary floristic patterns along the inundation forests of the Negro River. © 2013 Elsevier Ltd.
Keywords: Amazonian floodplain forests; Floristic variation; Fluvial-geomorphology; Holocene; Igapó; Negro River; basal area; deposition; erosion; flooding; floodplain forest; floristics; fluvial geomorphology; macroecology; river channel; vegetation; Amazonia; Rio Negro [South America]